2002
DOI: 10.1002/jmri.10140
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of clinically benign and malignant breast lesions using diffusion‐weighted imaging

Abstract: Purpose:To evaluate the value of diffusion-weighted imaging (DWI) in distinguishing between benign and malignant breast lesions. Materials and Methods:Fifty-two female subjects (mean age ϭ 58 years, age range ϭ 25-75 years) with histopathologically proven breast lesions underwent DWI of the breasts with a single-shot echo-planar imaging (EPI) sequence using large b values. The computed mean apparent diffusion coefficients (ADCs) of the breast lesions and cell density were then correlated. Results:The ADCs vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
604
8
26

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 667 publications
(690 citation statements)
references
References 27 publications
48
604
8
26
Order By: Relevance
“…Many studies report absolute threshold ADC values to differentiate benign and malignant lesions (6,7,(11)(12)(13)(14). However, all authors recommended other threshold ADC values, ranging from 1.10Á10 À3 to 1.60Á10 À3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies report absolute threshold ADC values to differentiate benign and malignant lesions (6,7,(11)(12)(13)(14). However, all authors recommended other threshold ADC values, ranging from 1.10Á10 À3 to 1.60Á10 À3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
“…Many different strategies have been proposed to increase the specificity such as calculating pharmacokinetic contrast parameters (4), T2*-weighted perfusion imaging (5) and MR spectroscopy (5). A promising adjunct MRI technique is diffusion-weighted imaging (DWI) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In DCE Breast MRI, lesions are characterized based on morphology, internal enhancement, and kinetic enhancement pattern (16,17).…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning MR protocols other than DCE-MRI, diffusion-weighted MR imaging (DWI) and MR spectroscopy (MRS) have recently been reported to demonstrate usefulness in differentiating benign from malignant breast lesions (11)(12)(13)(14)(15)(16)(17)(18). Since the report by Kinoshita et al (11) in 2002, recent studies using DWI have shown that apparent diffusion coefficient (ADC) values can be useful in differentiating between benign and malignant breast lesions (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Since the report by Kinoshita et al (11) in 2002, recent studies using DWI have shown that apparent diffusion coefficient (ADC) values can be useful in differentiating between benign and malignant breast lesions (11)(12)(13)(14)(15). Diffusion-weighted MRI is a specific modality that produces in vivo images of biological tissues weighted with the local microstructural characteristics of water diffusion.…”
mentioning
confidence: 99%